Metabolite Profiling and Comparison of Bioactivity in Antrodia cinnamomea and Antrodia salmonea Fruiting Bodies - Chen, Chieh-Yin; Chien, Shih-Chang; Tsao, Nai-Wen; Lai, Chiem-Sing; Wang, Ya-Yun; Hsiao, Wen-Wei; Chu, Fang-Hua; Kuo, Yueh-Hsiung; Wang, Sheng-Yang (Planta Medica, 2016)
Antrodia cinnamomea is a precious edible mushroom endemic to Taiwan that has been claimed to have significant health promotion activities. Antrodia salmonea is a new species of the genus Antrodia. In this study, we compared the metabolites and bioactivity of A. cinnamomea and A. salmonea fruiting bodies. The volatiles of A. cinnamomea and A. salmonea were characterized and 3,4,5-trimethoxybenzaldehyde was found to be the most abundant compound in A. cinnamomea; the other abundant compounds were δ-guaiene, isolongifolene, 1-octen-3-ol, 4-terpinenol, α-guaiene, and p-cymene. In A. salmonea, the main volatiles were α-cedrene, 1-octen-3-ol, D-limonene, cadinadiene, germacrene D, isolongifolene, and α-muurolene. Furthermore, five ergostane-type triterpenoids and two lanostane-type triterpenoids were selected as index compounds characterizing A. cinnamomea and A. salmonea extracts. The content of each compound varied between the two species. (R,S)-antcin B was the most abundant compound in A. cinnamomea fruiting bodies (75.18 ± 0.11 µg/mg). However, (R,S)-antcin C (184.85 ± 0.96 µg/mg) was the major triterpenoid in the A. salmonea fruiting body. Furthermore, two compounds, antcin M and methyl antcinate K, were only present in the A. salmonea fingerprint; therefore, antcin M and methyl antcinate K may be important for distinguishing between A. cinnamomea and A. salmonea fruiting bodies. Finally, examination of anti-inflammation activity and cytotoxicity showed that A. salmonea had more anti-inflammatory activity than A. cinnamomea; however, A. salmonea was more cytotoxic than A. cinnamomea. In conclusion, the composition and bioactivity of the fruiting bodies of A. cinnamomea and A. salmonea varies. Therefore, it is recommended that further toxicological evaluation and investigation of the biological activity of A. salmonea is carried out to ensure its safe and efficacious use as an alternative to A. cinnamomea.
Keywords: Antrodia cinnamomea; Antrodia salmonea; Polyporaceae; metabolites profiling; anti-inflammatory activity; cytotoxicity